2017
DOI: 10.1002/ece3.3483
|View full text |Cite
|
Sign up to set email alerts
|

Internode morphometrics and allometry of Tonkin Cane Pseudosasa amabilis

Abstract: Pseudosasa amabilis (McClure) (Poales: Gramineae) is a typical bamboo species naturally distributed in large area of south China and famous for its culm strength. Although bamboos were found to share the same development rule, the detailed internode morphology of bamboo culm was actually not fully expressed. We explored internode morphology of P. amabilis using 11 different physical parameters in different dimensions (1–4). As Taylor's power law (TPL) is generally applicable to describe relationship between me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 29 publications
6
20
0
2
Order By: Relevance
“…Therefore, the scaling relationship of leaf weight and leaf area of bamboo plants is significantly stronger than those of the other two classes of plants based on the comparison of the coefficients of determination (i.e., R 2 ). Because the biomass (weight) is a better measurement than the area or length in describing TPL [18,23], plants with a better scaling relationship between leaf weight and leaf area will have a better TPL for describing leaf bilateral symmetry. If we could cut a leaf into different parts with equidistant intervals from the leaf base to leaf apex and measure their weights (see Figure 1), we believe that we would obtain a better goodness of fit for TPL by using the measures of leaf weight than using the measures of leaf area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the scaling relationship of leaf weight and leaf area of bamboo plants is significantly stronger than those of the other two classes of plants based on the comparison of the coefficients of determination (i.e., R 2 ). Because the biomass (weight) is a better measurement than the area or length in describing TPL [18,23], plants with a better scaling relationship between leaf weight and leaf area will have a better TPL for describing leaf bilateral symmetry. If we could cut a leaf into different parts with equidistant intervals from the leaf base to leaf apex and measure their weights (see Figure 1), we believe that we would obtain a better goodness of fit for TPL by using the measures of leaf weight than using the measures of leaf area.…”
Section: Resultsmentioning
confidence: 99%
“…These studies related to TPL have added to our understanding of the variation of a large number of ecological and non-ecological measures, for example, animal and plant population density, biomass, poikilothermic developmental rate, crime, precipitation, released energies of aftershocks, trading activity of stock, and so on [13,[18][19][20][21][22]. In our recent studies, weight is a typical representative of energy for biological measures, so the variance-mean relationship based on weight measures should reflect TPL well [23].…”
Section: Introductionmentioning
confidence: 99%
“…Taylor's power law (TPL) has been used to describe the relationship between the variance (V) and the mean (M) of population densities, and takes the form of V = aÁM b (Taylor 1961), where a represents a constant, and b is an empirical exponent ranging from 1 to 3 (Taylor 1981;Anderson et al 1982;Ballantyne and Kerkhoff 2007;Kaltz et al 2012;Giometto et al 2015;Cohen and Xu 2015;Xiao et al 2015;Shi et al 2016Shi et al , 2018Tippett and Cohen 2016). Taylor's power law has been applied and verified widely in many disciplines such as botany, ecology, economics, entomology, epidemiology, meteorology, and physics (Walgenbach 1994;Yamamura 2000;Eisler et al 2008;Kaltz et al 2012;Tippett and Cohen 2016;Cheng et al 2017;Cohen et al 2017a;Lin et al 2018;Shi et al 2017aShi et al , b, 2018. Multiple biological and ecological constraints affect the exponent b of TPL.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear how TPL of plant biomass is related to other laws of plant dimensions such as leaf area, stem diameter and tree height. Cheng et al (2017) analyzed TPL with reference to the internode variables for a bamboo Pseudosasa amabilis, including internode diameter, length, thickness, and weight, and found that the physical dimensions of these measures could significantly affect the goodness of fit to the log-log linear regression of TPL. TPL for weight yielded a better fit than did other parameters because weight (and biomass) represents the highest physical dimension among these measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation